Implementation of Goods and Services Procurement Agreement Between CV. Sabicho with SMP Negeri 2 Tasikmadu Karanganyar: Analysis Based on Presidential Regulation Number 12 of 2021 - Diana Setiawati; Rosita Rahmawati (Universitas Muhammadiyah Surakarta, 2023)
Procurement activities for government goods or services are included in civil legal relations because the organizer and the provider of goods or services actually sign a contract to meet the needs of the user of the goods or services. Procurement of goods or services is carried out through stages of the procurement process, where finally the selected provider of goods or services will sign an agreement/contract with the user of the procurement of goods or services. The agreement/contract contains an agreement between the official who is the first party procuring goods or services and the provider of goods or services who is the second party. The purpose of this research is to determine the implementation of the agreement and also the legal consequences if there is a default in the agreement for the procurement of goods and services. In this research, the method used is the juridical-normative (doctrinal) method which the author uses to analyze and describe agreements for the procurement of goods or services. The research results show that the implementation of the agreement to purchase goods or services signed by both parties is a standard agreement and the legal consequences arising from the agreement are in accordance with presidential regulation no. 12 of 2021 Amendment to Presidential Regulation no. 16 of 2018 regarding the procurement of government goods or services and also the Civil Code.